1990
DOI: 10.1111/j.1365-2222.1990.tb03150.x
|View full text |Cite
|
Sign up to set email alerts
|

House dust mite allergen levels and an anti‐mite mattress spray (natamycin) in the treatment of childhood asthma

Abstract: Natamycin, a fungicide marketed as Tymasil, is claimed to reduce house dust mite numbers and would therefore be expected to improve asthma in children with mite sensitivity. We have tested this assertion by a double-blind, placebo-controlled trial. There was no significant effect on levels of Der p I in mattress dust between active and placebo groups at the end of the spraying period. Histamine inhalation challenge PC20, clinic visit symptom scores and lung function tests reflecting either large or small airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 18 publications
2
22
1
1
Order By: Relevance
“…Six studies used chemical methods to reduce exposure to mites, 91112161724 13 used physical methods, 58131518 – 222526 and four used a combination of methods. 10111423 Five studies did not assess the reduction of the population of mites 615182226.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used chemical methods to reduce exposure to mites, 91112161724 13 used physical methods, 58131518 – 222526 and four used a combination of methods. 10111423 Five studies did not assess the reduction of the population of mites 615182226.…”
Section: Resultsmentioning
confidence: 99%
“…also Table 1 [124] 3-fold less airborne Der p I after use than with standard vacuum cleaner [125] cf. Table 1 [151,152,169] No published field trial data Abbreviations: P-C = placebo-controlled, T = treated/treatment group, C = control group. * = P<005, nos = numbers.…”
Section: No Published Field Trial Datamentioning
confidence: 99%
“…Whilst a number of acaricides have been shown to reduce mite densities and allergen concentrations, of two controlled clinical studies with children, both using Natamycin, one showed not only no change in clinical symptoms, bronchial hyper-reactivity and lung function, but also no change in allergen concentrations [151]. The other showed significantly reduced numbers of live mites and significantly improved symptom scores and medication use [152].…”
Section: Childhood Asthmamentioning
confidence: 99%
“…However, results are often disappointing (5) unless dramatic changes in living conditions are employed (6). The efficacy of acaricides or other chemicals in eliminating mites from the environment is still debated (7)(8)(9), and there is concern about possible long-term toxic side effects (4). The two studies that have achieved the best clinical results utilized measures that would not be practical in most situations (6,10).…”
mentioning
confidence: 99%